2014
DOI: 10.1016/j.neuron.2014.08.004
|View full text |Cite
|
Sign up to set email alerts
|

A Transcriptional Mechanism Integrating Inputs from Extracellular Signals to Activate Hippocampal Stem Cells

Abstract: SummaryThe activity of adult stem cells is regulated by signals emanating from the surrounding tissue. Many niche signals have been identified, but it is unclear how they influence the choice of stem cells to remain quiescent or divide. Here we show that when stem cells of the adult hippocampus receive activating signals, they first induce the expression of the transcription factor Ascl1 and only subsequently exit quiescence. Moreover, lowering Ascl1 expression reduces the proliferation rate of hippocampal ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
211
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(222 citation statements)
references
References 75 publications
10
211
0
1
Order By: Relevance
“…In particular, Ascl1 plays a crucial role in activating neural stem/ progenitor cells in the adult SVZ (Andersen et al, 2014). Analyzing the expression of Ascl1 at P10 and P21 showed a significant increase in the number of Ki67+/Ascl1+ proliferating neural stem/ progenitor cells in the caudal SVZ of COUP-TF double conditional mutant mice compared with control mice (8.7-fold increase at P10 and 10.8-fold increase at P21, Fig.…”
Section: Few Coup-tfii+ Cells Exist In the Adult Svz-rms-ob Pathwaymentioning
confidence: 91%
See 2 more Smart Citations
“…In particular, Ascl1 plays a crucial role in activating neural stem/ progenitor cells in the adult SVZ (Andersen et al, 2014). Analyzing the expression of Ascl1 at P10 and P21 showed a significant increase in the number of Ki67+/Ascl1+ proliferating neural stem/ progenitor cells in the caudal SVZ of COUP-TF double conditional mutant mice compared with control mice (8.7-fold increase at P10 and 10.8-fold increase at P21, Fig.…”
Section: Few Coup-tfii+ Cells Exist In the Adult Svz-rms-ob Pathwaymentioning
confidence: 91%
“…1J,K). A subset of NSCs and rapidly dividing intermediate progenitor cells have been shown to express the proneural basic helix-loop-helix transcription factor achaete-scute homolog 1 (Ascl1, also known as Mash1) (Parras et al, 2004;Kohwi et al, 2005;Kim et al, 2011;Andersen et al, 2014;Mich et al, 2014). By immunostaining for COUP-TFI and Ascl1, we found that many COUP-TFI+ cells in the adult SVZ expressed Ascl1 (Fig.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…In other words, without the existence of neural stem cells, self-repair would not be possible. In this direction, recent evidence supporting the key role of Ascl1 in determining the re-activation of Neural Stem Cells offers a promising approach to overcome cell dormancy [19]. The examination of the environmental cues and conditions promoting an increase in neurogenic activity will be fundamental to re-activate the latent neurogenic potential of the adult human brain therapeutically.…”
Section: Abstract: Cell Differentiation • Cell Migration • Neural Stementioning
confidence: 99%
“…Further, Oct1-2 in mammalians is related to Pdm1-2 in Drosophila [293]. In addition, Ascl1 i.e., the mammalian ortholog of Ase, induces daughter proliferation in the mouse adult brain [294,295].…”
Section: The Genetic Mechanisms Governing the Nb Identity Are Conservmentioning
confidence: 99%